PENDIDIKAN ISLAM DALAM PERSPEKTIF KECERDASAN JAMAK (MULTIPLE INTELLIGENCES) - Ansharullah Ansharullah (Instruksional, 2020)
AbstractThis research stems from a condition which was observed in Indonesian high school. In general  the schools do not implement the principles of multiple intelligences comprehensively. Conversely, it is still impressed that the  learning is still dominated by one intelligence based education,  that is IQ which is  cause and effect oriented eductional program. In line with that the learning is filled in the domain of cognition which is commonly oriented at the most basic level of mental development, in which the level of memorization activity is fulfilled the learning process. So that the complex intelligences of the learners’ do not develop optimally. This conditions produce that the  Indonesian educational products are not optimal. So to improve the quality of education, it is necessary to develop the implementation of learning system which based on the impact of the findings of neuroscience into education, including the development of multiple intelligences (multiple intelligences) in high school level. This research is a qualitative research seeing from philosophical approach and perspective. Along with that, the method used is descriptive, analysis and interpretive. Through philosophical approaches researcher tries to describe the essence of the eight intelligences and their applications in the learning process. With the method of description and interpretation, it is expected to be able to find an interpretation of the concept of multiple intelligences in accordance with socio-religious background of students’. Then by using the analysis method, the application of  these findings can be adjusted to the needs and potentials which is available at high school levelled education.